Weighting of Risks in Plastic Injection Moulding Machines Using the Hesitant Fuzzy SWARA Method - Duruel, Turgay; Gulsun, Bahadir (WORLD SCIENTIFIC PUBL CO PTE LTD, 2026)
This study is an original scientific approach that aims to evaluate the risks encountered in plastic injection moulding machines in terms of occupational health and safety in a more objective and sensitive manner. In the research, by going beyond the classical risk analysis methods, Unstable Fuzzy SWARA and CRITIC methods are integrated. Thus, expert opinions have been weighted and uncertainties have been minimized and a healthier ranking of risks has been provided. The prominent contributions and originalities of this study are as follows; 7 basic risks identified in the field of plastic injection moulding machines were evaluated with both fuzzy logic and classical FMEA method and the results were compared. The weights of the experts according to their sectoral experience were determined by CRITIC method and these weights were integrated into the analysis process. Unstable Fuzzy SWARA provided a more flexible analysis by taking into account the conflicting or hesitant assessments of the experts. The highest risk factor was identified as 'Failure to maintain the workbench' and this finding is an important warning in terms of production continuity and occupational safety. While in the classical analysis with FMEA, some risks were evaluated equally, the proposed approach produced a sharper ranking by differentiating each risk. A comparison with the Kendall Tau correlation coefficient showed only 33% similarity between the two methods. This indicates that the new method better reflects decision-maker diversity and uncertainties. As a result, the study is applicable not only to the plastic injection moulding industry but also to multi-criteria and uncertain risk assessments in different industrial systems. The developed model makes an innovative contribution to the literature in terms of decision-maker diversity and evaluation flexibility, and produces more reliable and actionable results.
Keywords: Occupational health and safety; SWARA; hesitant fuzzy sets; CRITIC; FMEA; risk weighting; machine maintenance; Engineering